Moderate selenium mitigates hand grip strength impairment associated with elevated blood cadmium and lead levels in middle-aged and elderly individuals: insights from NHANES 2011–2014 - Liang, Yafeng; Wang, Junqi; Wang, Tianyi; Li, Hangyu; Yin, Chaohui; Liu, Jialin; Wei, Yulong; Fan, Junxing; Feng, Shixing; Zhai, Shuangqing (Frontiers in Pharmacology, 2023)
Background: Selenium (Se) has been reported to have an antagonistic effect on heavy metals in animals. Nevertheless, there is a lack of epidemiological research examining whether Se can mitigate the adverse effects of cadmium (Cd) and lead (Pb) on hand grip strength (HGS) in middle-aged and elderly individuals. Methods: This study used data from the 2011-2014 National Health and Nutrition Examination Survey (NHANES). HGS measurements were conducted by trained examiners with a dynamometer. Concentrations of Se, Cd, and Pb in blood were determined via inductively coupled plasma mass spectrometry. We employed linear regression, restricted cubic splines, and quantile g-computation (qgcomp) to assess individual and combined associations between heavy metals and HGS. The study also explored the potential influence of Se on these associations. Results: In both individual metal and multi-metal models adjusted for confounders, general linear regression showed Se's positive association with HGS, while Cd and Pb inversely related to it. At varying Se-Cd and Se-Pb concentrations, high Se relative to low Se can attenuate Cd and Pb's HGS impact. An inverted U-shaped correlation exists between Se and both maximum and combined HGS, with Se's benefit plateauing beyond approximately 200μg/L. Stratified analysis by Se quartiles reveals Cd and Pb's adverse HGS effects diminishing as Se levels increase. Qgcomp regression analysis detected Se alleviating HGS damage from combined Cd and Pb exposure. Subsequent subgroup analyses identified the sensitivity of women, the elderly, and those at risk of diabetes to HGS impairment caused by heavy metals, with moderate Se supplementation beneficial in mitigating this effect. In the population at risk for diabetes, the protective role of Se against heavy metal toxicity-induced HGS reduction is inhibited, suggesting that diabetic individuals should particularly avoid heavy metal-induced handgrip impairment. Conclusion: Blood Cd and Pb levels are negatively correlated with HGS. Se can mitigate this negative impact, but its effectiveness plateaus beyond 200μg/L. Women, the elderly, and those at risk of diabetes are more vulnerable to HGS damage from heavy metals. While Se supplementation can help, its protective effect is limited in high diabetes risk groups.